2020
DOI: 10.18502/kss.v4i6.6615
|View full text |Cite
|
Sign up to set email alerts
|

Using the Blended Learning to Enhance Students’ Engagement and Learning Experience in Taxation

Abstract: This paper examines the student engagement and learning experience in taxation course using blended learning. Blended learning is a combination of face-to-face learning experiences and online learning experiences which aim to complement each other in order to support and enhance student learning. This paper presents the research findings questionnaire surveys of students who currently study taxation courses. The questionnaire was developed and sent to all taxation undergraduate course in Faculty of Economics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It is imperative for educational institution to invest time and other resources to develop and maintain a successful blended learning environment and internet capacity. Furthermore, a substantial time commitment is also needed at the start-up phase and continued maintenance throughout (Setiyani et al, 2020;Marikyan and Papagiannidis, 2021). As shown in the results, e-learning system increases lecture performance, create possibilities for lecturing advancement, and develop competence (Mahande & Malago, n.d.).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative for educational institution to invest time and other resources to develop and maintain a successful blended learning environment and internet capacity. Furthermore, a substantial time commitment is also needed at the start-up phase and continued maintenance throughout (Setiyani et al, 2020;Marikyan and Papagiannidis, 2021). As shown in the results, e-learning system increases lecture performance, create possibilities for lecturing advancement, and develop competence (Mahande & Malago, n.d.).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Thus, Manalo and Benavides (2021) found in their survey that it was vital for teachers to be technologically prepared in teaching. In addition, Setiyani et al (2020), identified that an educational institution must be prepared to invest time and other resources to develop and maintain a successful blended learning environment and internet capacity.…”
Section: Technology Preparedness In Sciencementioning
confidence: 99%
“…One of the greatest leaps lecturers have ever made towards realising meaningful progress in student engagement is through the use of blended learning methods (Setiyani et al, 2020). Blended learning has been defined as a formal educational strategy in which a student learns at least in part through online delivery of content and instruction with some element of student control over time, pace, path, and/or place, and in part through traditional face-to-face instruction in a brick-andmortar location away from home (Kim, 2013;Min & Wu, 2017;Staker & Horn, 2012).…”
Section: Blended Learning: Technology Enhanced Student Engagementmentioning
confidence: 99%
“…In proposing these strategies, the role of the lecturer as that of encouraging learning by facilitation, and coordinating the co-creation of understanding with learners and between learners is considered. Setiyani et al (2020) argue that this way, Educators build learners into the curriculum design by giving learners control over parts of their learning environment; this includes creating learning-oriented assessment designs. This requires setting up the conditions such as the group, technology or blend, and to design learning activities which are divisible by the number of group members, and are interdependent which means each group member has a structured job to do and is more likely to encourage individuals to actively engage with learning (p. 389).…”
Section: Technology Integration Strategies For Enhanced Student Engag...mentioning
confidence: 99%
“…The principles and practices of experiential learning have been widely adopted in models, programs to conduct academic courses such as competency-based education (Miettinen, 2000;Ahmed, 2018), professional training (Richard, Cowen & Kolb, 1995;Akhigbe, 2018;Amolloh, Lilian & Wanjiru, 2018;Tiessen, Grantham & Cameron, 2018;Stefano, Ruvolo & Mauro, 2019), college programs for adult learners, and prior learning assessment (Simosko, 1998;Andrews, Brown & Mesher, 2018;Awidi & Paynter, 2019;Bhati & Song, 2019), service learning (Angela, Bruce, Kevin, Mandar & Kurtis, 2011;Aissaoui, Alami, Oughdir & Allioui, 2018), problem-based learning (Bethell & Morgan, 2011;Gomez & Nasir, 2019;Harfitt, 2019;Stephanie, Lockwood, Hill & Randell, 2020;Setiyani, Harnanik, Lianighsih & Susilowati, 2020), action learning (Louise, 1994). The experiential lessons provide students with an opportunity to experience concepts, give students a more productive, more meaningful understanding of course concepts, and of how they operate in the real world.…”
Section: The Process Of Instruct Students To Perform Experiential Learning Activities In the Schoolsmentioning
confidence: 99%